2016
DOI: 10.1016/j.diabres.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life and family impact of type 1 diabetes among adolescents in Saudi Arabia

Abstract: These findings emphasize the importance of an interdisciplinary, biopsychosocial and family centered care approach to adolescents with a chronic disease. Future work could assess the effectiveness of direct care involvement of adolescent and mental health experts in improving the HRQoL for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 36 publications
10
42
2
4
Order By: Relevance
“…On the contrary, Abdul-Rasoul et al (2013) [18] reported that male gender predicted better QOL, as girls have been shown to have more diabetes-related worries which is conformed to the results of AlBuhairan et al (2016) [19] While Monazea et al (2012) [28] reported that female children with diabetes had total score QOL less than males but with no significant…”
Section: Published By Sciedu Presssupporting
confidence: 42%
See 2 more Smart Citations
“…On the contrary, Abdul-Rasoul et al (2013) [18] reported that male gender predicted better QOL, as girls have been shown to have more diabetes-related worries which is conformed to the results of AlBuhairan et al (2016) [19] While Monazea et al (2012) [28] reported that female children with diabetes had total score QOL less than males but with no significant…”
Section: Published By Sciedu Presssupporting
confidence: 42%
“…Also Laffel et al (2003), [25] and Vanelli et al (2003) [26] reported no effect of age or the duration of diabetes regarding the QOL. While in the contrary, Abdul-Rasoul et al (2013) [18] and AlBuhairan et al (2016) [19] reported that age of the patient was an important predictor of QOL as children got older, the scores improved.…”
Section: Published By Sciedu Pressmentioning
confidence: 94%
See 1 more Smart Citation
“…There was no significant difference in quality of life between two reports, whereas parents evaluation of quality of life was not significantly different than children's evaluation (p. value = .73), this finding was not aligned with study conducted in Saudi Arabia where it is significantly different [13]. Although it's significantly different in emotional dimension (p. value = .03) that could be due to differences of perception and worrying between adult and children.…”
Section: Discussioncontrasting
confidence: 63%
“…""Worry"" subscale had the lowest scores reported by both adolescents and parents. [27] In another group, 214 adolescents (13-18 years) with T1DM were surveyed to assess HRQoL at Diabetes Treatment Center, Prince Sultan Military Medical City, Riyadh, KSA from Jun. to Sep. 2013.…”
Section: Materials and Method:-mentioning
confidence: 99%